Local adaptation of phenology revealed in outcrosses between spawning segments of a salmonid population. Issue 23 (22nd November 2018) - Manhard, Christopher V.; Adkison, Milo D.; Hard, Jeffrey J.; Smoker, William W.; Gharrett, Anthony J.
Abstract: Local adaptation has been demonstrated in spatially or temporally distant animal populations but seldom in proximate populations. To address the scale of local adaptation in Pacific salmon ( Oncorhynchus spp.), two generations of hybrids between temporally separated spawning segments were made in a population of pink salmon ( O. gorbuscha ) and compared with controls to evaluate the genetic architecture underlying adult migration time and to test for declines in marine survival that resulted from outbreeding depression. Bayesian mixed‐effects models revealed that adult migration times in hybrid lines were intermediate to those of controls and that additive sources of genetic variation were significant, thereby indicating that local adaptation has acted on additive genetic variation in shaping this trait. Similarly, a line cross analysis revealed that an additive model best described the genetic architecture of adult migration time. In contrast, marine survival was generally similar between control and hybrid lines, which suggested that the effect of outbreeding upon marine survival was minimal at such a fine scale of genetic divergence. The implications of these results are that (a) local adaptation can facilitate genetic divergence of life history traits between proximate subpopulations; (b) artificial relaxation of natural barriers to gene flow can cause maladaptive shifts in life history traits; and (c) wild populations may harbour fine‐scale adaptive variation that supports productivity and sustainability.